Synthesis Optimization and Antibacterial Performance of Colloidal Silver Nanoparticles in Chitosan - Endang Susilowati; Lina Mahardiani; Sri Retno Dwi Ariani; Ilham Maulana Sulaeman (Universitas Gadjah Mada, 2023)
Colloidal silver nanoparticles were successfully synthesized via the chemical reduction method. The synthesis used AgNO3 as the precursor, chitosan as the reducing and stabilizing agents, and NaOH as the accelerator. The synthesis parameters were optimized. The samples were tested with a UV-vis spectrophotometer to observe their localized surface plasmon resonance (LSPR) phenomenon, a transmission electron microscope (TEM), and a particle size analyzer (PSA) to investigate their particle shape and size distribution. Further, silver nanoparticles were tested for their storage stability and antibacterial performance. The UV-vis spectroscopy data exhibited that the silver nanoparticles have been successfully synthesized, validating via the emergence of the LSPR absorption band at 402–418 nm. At 50 °C, the optimum synthesis was achieved for 100 min of reaction time by adding 0.033 M NaOH and AgNO3 4.00% (w/w, AgNO3/chitosan). TEM results showed spherical silver nanoparticles of 1–8 nm, while the PSA results exhibited particles sizes of about 12–59 nm. The colloidal silver nanoparticles were stable in storage for 8 weeks and had good antibacterial performance against E. coli, S. aureus, extended-spectrum beta-lactamases (ESBL), and methicillin-resistant S. aureus (MRSA). Therefore, colloidal silver nanoparticles have the potential as a material for medical applications.